Transgender Health: A Standardized Patient Case for Advanced Clerkship Students - Kelly Underman; Danielle Giffort; Abbas Hyderi; Laura E. Hirshfield (Association of American Medical Colleges, 2016)
Abstract Introduction Transgender patients experience poor health outcomes and often avoid seeking medical care because of negative encounters with providers. Despite growing awareness of the health disparities transgender patients face, there is very little curricular time in medical schools to improve medical students' knowledge and skills for caring for transgender patients. This standardized patient (SP) case was developed for use in a communication challenges workshop for advanced clerkship students in order to address working with transgender patients. Methods This formative SP encounter takes place in a classroom as part of a half-day workshop on communication challenges with patients. We developed the case to focus specifically on skills related to obtaining patients' preferred names and pronouns, as well as taking an appropriate patient history. Materials for SP recruitment, SP training, and case implementation are included within this publication. Results In preliminary uses of the case, 80% of students (N = 64) agreed or strongly agreed that it had increased their skills for working with transgender patients. Observational data from the debrief discussions also revealed that medical students perceived gaps in their medical training regarding LGBT health and expressed interest in their program incorporating more information on transgender health. Discussion This case adds to a growing number of curricular interventions to address medical students' knowledge and skills with regard to lesbian, gay, bisexual, and transgender (LGBT) patients and, as a result, aims to address health disparities in LGBT patient populations.